The Economic Perspective of Colombia in 2023 (2023)
The world economy is going through a complex moment, which may lead to an economic recession accompanied by high and long-lasting inflation,  with repercussions for economic activity in general terms. To contain  inflation in all countries, including Colombia, central banks have used a contractionary monetary policy. In the case of the United States, the Federal Reserve has been increasing interest rates, which has allowed the strengthening of the dollar against the euro and other currencies of developed countries, and some currencies of developing countries such as Colombia. This situation has allowed financial investors to prefer to demand more dollars because it provides them with higher profitability.